In-service English teachers’ motivations in the Indonesian teacher profession education program - Apoko, Tri Wintolo; Cahyono, Bambang Yudi (International Journal of Evaluation and Research in Education (IJERE), 2024)
To be certified as professional English teachers, Indonesian teachers must complete the teacher profession education program (TPEP) offered by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. Due to a lack of discussion and research on the motivation of inservice English teachers participating in the TPEP, this study explored the TPEP-related motivation of in-service English teachers. There were 80 inservice English teachers who joined the TPEP at a reputable private university in Indonesia participated in this mixed-method study. A survey questionnaire was distributed to the in-service teachers to know their motivation regarding the TPEP. The findings indicated that the majority of the in-service English teachers were highly motivated to participate in the TPEP. They also thought that TPEP was beneficial for teachers as it enhanced their knowledge and skills in teaching. Through the TPEP they learned to use innovative strategies to teach English such as project-based learning and problem-based learning. This implies that more in-service English teachers should be encouraged to join TPEP to develop their competencies.